2002
DOI: 10.1159/000048922
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Effect of Aluminium on the Catalase Activities of the Brains of Two Species of Poikilothermic Vertebrates

Abstract: Background: Although aluminium (Al) has been implicated in various neuropathological states with aging due to its involvement in neurotoxicity, the exact role of the metal ion is still unclear. Objective: The aim of the present study is to ascertain whether the antioxidant enzymes of the brain protecting from oxidative damages which accumulate with aging are regulated by Al in an age-dependent manner. Method: The inhibitory effect of Al on the catalase activity of brain homogenates of two species of poikilothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Maturity in respect to the age of the species may also be responsible for variation in measured morphometric parameters. Although the age of the specimens was not considered in this study, the report of Jena et al [29] showed that young lizards morphometric parameters are lower when compare with the older ones.…”
Section: Resultsmentioning
confidence: 91%
“…Maturity in respect to the age of the species may also be responsible for variation in measured morphometric parameters. Although the age of the specimens was not considered in this study, the report of Jena et al [29] showed that young lizards morphometric parameters are lower when compare with the older ones.…”
Section: Resultsmentioning
confidence: 91%
“…Garg et al [33] have observed antiulcer effects of neem leaves in rats exposed to restraintcold stress or ethanol orally. Neem leaf extract was found to reduce ulcer index, free and total acidity, and the volume of gastric acid secretion [34]. Neem leaves are reported to exert antiulcer effects by preventing mucus depletion and mast cell degranulation.…”
Section: Antiulcerogenic Activitymentioning
confidence: 99%
“…The enzyme activity, initially increased to compensate for the oxidative stress, is depleted by extended exposure, leading to protein and DNA damages [ 66 ]. A significant decrease in the brain catalase (CAT) activity was observed in Channa punctatus , C. idella , and O. mossambicus exposed to AlCl 3 , Al 2 (SO 4 ) 3 , and Al 2 O 3 NPs, respectively [ 61 , 66 , 67 ]. The decrease was linked to the production of glutathione peroxidase (GPx), an antioxidant enzyme, in competition with CAT for the common hydrogen peroxide (H 2 O 2 ) substrate [ 74 ] and with the establishment of non-enzymatic mechanisms as, for example, the sequestration of oxidant radicals by metallothioneins [ 75 ].…”
Section: Effects Of Aluminium On the Nervous System Of Freshwater Aquatic Vertebratesmentioning
confidence: 99%
“…In D. rerio, Lepomis macrochirus, Rutilus rutilus, Carassius carassius, and Neogobius fluviatilis, a significant increase in the level of brain lipid peroxidation was seen after exposure to AlCl 3 [70,73]. This accumulation was also observed in C. idella exposed to Al 2 (SO 4 ) 3 [66] and in Oreochromis mossambicus after exposure to Al oxide nanoparticles (Al 2 O 3 NPs) [67].…”
mentioning
confidence: 95%